THE IMPORTANCE OF LEARNING AND KNOWING ENGLISH IN HIGHER EDUCATION IN INDONESIA - Endang Sri Andayani (Universitas Indraprasta PGRI, 2022)
In this day and age of globalization, studying English is a critical skill that students must master. This is due to the fact that practically all scientific publications and information sources on the internet are written in English. Aside from that, practically all businesses in the world of work require English language abilities when hiring new employees. Higher education, as the final step from the school's perspective to entering the world of employment, must be able to produce students who, in addition to having expertise in their disciplines, can also communicate in English. As a result, the purpose of this research is to examine the significance of studying English to university students in Indonesia in order to develop superior human resources capable of competing in the workplace. This study employs a qualitative method with a descriptive approach by taking several universities in Jakarta The study's findings indicate that learning English in addition to Indonesian is now required in tertiary institutions because students must be able to understand and be fluent in the field of science they are studying, as well as communicate effectively, because the majority of their scientific sources are derived from scientific sources that use English. However, although there is a growing desire in learning English, the researchers discovered four barriers: a lack of teachers, a lack of motivation as a result of being considered unconnected to the study program, a lack of infrastructure, and viewing it as a waste. According to the findings of this study, universities in Indonesia have begun to incorporate English language learning into their curricula as a preparation for students to compete in the global world of work, where they are not only experts in their fields but also fluent in communicating in English